Likelihood of impact events in transport networks considering road conditions, traffic and routing elements properties - Strauss, Alfred; Moser, Thomas; Honeger, Christian; Spyridis, Panagiotis; Frangopol, Dan M. (Journal of Civil Engineering and Management, 2020)
A large number of transport infrastructure equipment are located along the driving lanes of roadways, which must be secured by restraint systems. Among others, the different road lanes must be adequately separated from each other. The investigations reported herein aim to provide a probabilistic approach for the departure of motor vehicles from their intended lane and impact oν restraint systems. Currently, evaluations of the road infrastructure against possible accidents are mostly focused on the resistance side. This contribution, however, intends to address the action side, focusing in particular on the probability of impact of vehicles on the road furniture. The main parameters taken into account are the geometry of the road and the traffic composition and characteristics. The objective of this research is to develop an analysis tool for the probability-based assessment of vehicles departing from their driving lane. The analysis tool for the determination of the likelihood of impact events in transport networks, requires to define (a) of the alignment (longitudinal inclination, transverse inclination, and curvature of the lanes), (b) of the pavement conditions (lane grooves, road grip, and pavement cracks etc.), and (c) of the traffic composition as significant input parameters. These were investigated together with the road infrastructure operators. A newly introduced methodology is presented herein taking into account the above mentioned parameters and factoring in characteristic properties in order to assess the fragility of the infrastructure sub-system. The evaluation is based on either road engineering physics or expert judgements. The method is incorporated in a spreadsheet tool, which is also presented, the feasibility of this tool is demonstrated, and sensitivities of the assessment process are evaluated and discussed.